2010
DOI: 10.1021/pr100798r
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome-Wide Association Study Identifies Multiple Biomarkers that Discriminate North and South Chinese Populations at Differing Risks of Cardiovascular Disease: INTERMAP Study

Abstract: Rates of heart disease and stroke vary markedly between north and south China. A 1H NMR spectroscopy-based Metabolome-Wide Association approach was used to identify urinary metabolites that discriminate between southern and northern Chinese population samples, to investigate population biomarkers that might relate to the difference in cardiovascular disease risk. NMR spectra were acquired from two 24-hour urine specimens per person for 523 northern and 244 southern Chinese participants in the INTERMAP Study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 51 publications
4
93
0
2
Order By: Relevance
“…Metabolic alterations in urine have been studied for many conditions, including blood pressure and cardiovascular risk, cancer, and pregnancy disorders. 71,76,77 12…”
Section: The Human Metabolomementioning
confidence: 99%
“…Metabolic alterations in urine have been studied for many conditions, including blood pressure and cardiovascular risk, cancer, and pregnancy disorders. 71,76,77 12…”
Section: The Human Metabolomementioning
confidence: 99%
“…BCAA leucine and the products of BCAA reflect differences in gluconeogenesis (GNG) (16) in MD compared to the control diet (LFD). Moreover, these results could suggest a particular importance of BCAAs in lipid oxidation and ketone body synthesis.…”
Section: Metabolites From Protein Lipid and Carbohydrate Metabolic Pmentioning
confidence: 99%
“…The results showed that the development process of lung cancer was closely related to potential biological markers, including hippurate, gourd trigonelline, β-hydroxyisovaleric acid, α-hydroxyisobutyric acid, N-aceglutamide, and creatine anhydride. Kim et al, 2010 To be continued Higher in the north: dimethylglycine, alanine, lactate, branched-chain amino acids (isoleucine, leucine, valine), N-acetyls of glycoprotein fragments (including uromodulin), N-acetyl neuraminic acid, pentanoic/heptanoic acid, and methylguanidine; higher in the south: hippurate, 4-cresyl sulfate, phenylacetylglutamine, 2-hydroxyisobutyrate, succinate, creatine, scyllo-inositol, proline betaine, and trans-aconitate Yap et al, 2010b PubMed search (access: Aug. 26, 2016) revealed 154 publications of which 29 review articles were identified. Twenty-seven and 38 were original research papers filtered by the additional keywords "urine" and "serum", respectively.…”
Section: Fig 1 Nmr-based Metabolomics Workflowmentioning
confidence: 99%